Pencemaran Pada Selat Internasional dan Tanggung Jawab Negara Pemilik Kapal - Samuel, Wayan Dharmayana; Kainama, Marthinus; Peilouw, Johanis Steny Franco (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The many phenomena of sea pollution that often occur, especially in international straits as a result of ship activities, make this problem an urgent matter. Considering that Indonesia is an archipelagic country with a total of 17,500 islands and 70% of the sea area and only 30% of the land area.Purposes of the Research: The purpose of writing in this research is to know and understand the regulation of international law of the sea for pollution that occurs in international straits and to know and understand the responsibilities of ship-owning states based on international law.Methods of the Research: Qualitative analysis research method, normative legal research type, problem approach using three problem approaches namely statutory approach, conceptual approach and case approach. Source legal materials primary legal materials, secondary legal materials and also tertiary legal materials.Results of the Research: The results of the study prove that pollution in international straits has been regulated in an international law, namely in the 1982 UNCLOS, and in terms of the responsibility of the ship owner state adheres to the principle of absolute responsibility (strict liability) as stated in the 1969 CLC but not all cases can be Using this principle, only cases that have a large impact on the environment can use this principle, for example the case of an oil spill in a country's marine environment.